Constructivism Today: Constructivist Approaches in Education - José Manuel Serrano; Rosa María Pons Parra (Universidad Autónoma de Baja California, 2011)
This article presents an analysis of constructivism and constructivist approaches in education, and establishes a system of spatial coordinates in which different approaches are located, so as to place them then, on an established continuum based on the mechanisms and on the inter-mental and intra-mental components in play in the process of knowledge construction. After a brief discussion of these approaches and theories, we analyze the general structure underlying them all and locating a possible constructivist approach in the area of competencies. This is done by means of a constructivist analysis of teaching and learning processes, based on the concept that this idea engenders the project Definition and Selection of Competencies. We conclude with a possible work agenda offered by constructivism as the next challenge.